CONTEXTUAL VARIABILITY IN THE ACCEPTABILITY OF KENYAN ENGLISH GRAMMATICAL FEATURES1 (The University of Nairobi Journal of Language and Linguistics, 2023)
The present study set out to find out whether a number of grammaticalfeatures assumed to be characteristic of Kenyan English would beaccepted at different levels depending on three parameters of linguisticcontext: the lexical item used in the feature2 under study, the positionof the feature in the sentence, and the type of sentence which thefeature appears in. A two-part questionnaire consisting of a series ofsentences containing “mistakes” to be corrected was administered to anoverall sample (composed of eight sub-samples) of 218 educated KenyanEnglish speakers. The results, based on chi-square statistics, show that astructure like Type for me this letter was significantly more accepted(that is less often corrected) than Buy for me lunch, that when thefeature under study was placed within the sentence it tended to bemore accepted than when it was placed at the beginning or at the end ofthe sentence, and that question structures were more accepted thandeclarative and negative ones.